Functional disability for mobility in adults: a population-based study - Cristhiane Yumi Yonamine; Tiemi Matsuo; Regina Kazue Tanno de Souza; Mathias Roberto Loch; Marcos Aparecido Sarria Cabrera
Abstract Introduction: Functional disability is an important health indicator associated with worse quality of life. Objective: To estimate the prevalence of functional disability for mobility and to identify factors associated with difficulty going up and down stairs in adults aged 40 years or over. Methods: Cross-sectional, population-based study, with residents of the Municipality of Cambé, PR, interviewed in 2011. The dependent variable was the difficulty of going up and down stairs. Analysis of associated factors was performed using Poisson regression for each subgroup (40 - 59 years and 60 years or older). Results: In total, 24% of the subjects presented some kind of difficulty going up stairs (p < .01). In both subgroups, a significantly higher prevalence in women, among those inactive during leisure time and those with a history of cerebrovascular disease was observed. In the subgroup aged 40 to 59 years, age 50 - 59 years, hypertension, diabetes and falls in the previous 12 months were also associated with the outcome. Conclusion: The results suggest the need to expand the actions of health promotion, prevention and control of chronic conditions, especially among middle-aged people.